2014
DOI: 10.1002/mgg3.98
|View full text |Cite
|
Sign up to set email alerts
|

Ten new ATM alterations in Polish patients with ataxia‐telangiectasia

Abstract: Inherited biallelic mutations of the ATM gene are responsible for the development of ataxia telangiectasia (AT). The objective of the present study was to conduct molecular analysis of the ATM gene in a cohort of 24 Polish patients with ataxia-telangiectasia with aim being to provide an updated mutational spectrum in Polish AT patients. As a result of molecular analysis, the status of recurrent mutation was confirmed and ten new ATM variants were detected. Application of MLPA analysis allowed the detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A few recurring mutations in the ATM gene have been detected in Polish ataxia-telangiectasia patients. Three of the mutations, c.6095G > A, c.7630-2A > C and c.5932G > T, were the most frequent [ 27 , 28 ]. A mutation at position 5932 creates a stop codon and changes a GAA codon, specifying glutamine, into a UAA.…”
Section: Discussionmentioning
confidence: 99%
“…A few recurring mutations in the ATM gene have been detected in Polish ataxia-telangiectasia patients. Three of the mutations, c.6095G > A, c.7630-2A > C and c.5932G > T, were the most frequent [ 27 , 28 ]. A mutation at position 5932 creates a stop codon and changes a GAA codon, specifying glutamine, into a UAA.…”
Section: Discussionmentioning
confidence: 99%
“…A deletion of the last 2 exons of ATM (62–63) was detected in patient 32. Deletions of exon 63 or exons 62–63 of the ATM gene have previously been reported in patients with ataxia telangiectasia and are considered to be functionally relevant [ 39 , 40 ]. In two further patients (60, 40), we detected previously described ATM nonsense variants; the variant ATM:p.(Glu1978*) has been reported in BC cases before [ 41 ], whereas the variant ATM:p.(Cys2931*) has been described as a class 5 variant in a patient with ataxia telangiectasia [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al reported the heterozygous state in an A-T patient with a CNV in exon 63 and a nonsense variant (c.3174G > A) in exon 22 whose ataxia-age at onset was 48 months and serum levels of IgG, IgA, IgM, and Ig E were normal [ 18 ]. Podralska et al identified a CNV of exons 62 and 63, combined with a nonsense variant c.5932G > T in exon 42 [ 40 ]. A general summary of the characteristics of the atypical A-T with compound heterozygous SNV and CNV in ATM are shown in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Atypical A-T is frequently associated either with missense or leaky splice site variants that allow for some ATM protein with residual ATM kinase activity to be formed [ 32 ]. Podralska et al reported a compound heterozygous with 2 CNVs in ATM that was related mixed phenotype involving onset of ataxia at 2 years old, decreased level of immunoglobulins and normal level of AFP [ 40 ]. Previous reports described mixed phenotypes encompassing typical and atypical clinical features in the atypical A-T patients with compound heterozygous SNV and CNV in ATM [ 18 , 37 , 39 – 42 ].…”
Section: Discussionmentioning
confidence: 99%